HUBUNGAN SENAM OSTEOPOROSIS DENGAN AKTIVITAS SEHARI HARI USIA LANJUT DI PUSKESMAS PADANG BULAN MEDAN - Purba, Dahlia; Rokhima, Vitri (Jurnal Keperawatan Priority, 2023)
The public is encouraged to make promotive and preventive efforts, by adopting a healthy lifestyle smartly, namely periodic health checks, getting rid of cigarette smoke, diligent osteoporosis exercises, healthy and balanced diet, adequate rest, and managing stress. The purpose of this study was to determine the relationship between osteoporosis exercise and the daily activities of the elderly at the Padang Bulan Health Center. This study used a correlation descriptive design with a cross sectional approach with 30 respondents using the total sampling method. In the study, it was found that most of the respondents in the elderly age group were 20 respondents (66.7%) and a small proportion of respondents in the old age group were 10 people (33.3%). The results of the research conducted by the author showed that the correlation coefficient between osteoporosis exercise and daily activities of the elderly was 0.745. That is, p-value <α (0.000<0.05). This means that there is a significant relationship between osteoporosis exercise and daily activities for the elderly. The conclusion in this study is that there is a relationship between osteoporosis exercise and the daily activities of the elderly at the Padang Bulan Health Center.